Effects of methanol on the synthesis of aspartame precursor catalysed by Pseudomonas aeruginosa elastase - Lee, K.H.; Lee, P.M.; Siaw, Y.S.; Morihara, K. (Kluwer Academic Publishers, 1992)
Pseudomonas elastase was found to be efficient in catalysing the reaction between N-benzyloxycarbonyl-L-aspartic acid and L-phenylalanine methyl ester producing the aspartame precursor in aqueous and aqueous methanolic solutions. 25% (v/v) methanol was most favourable for the synthesis where about 100% increase in yield was obtained compared to that in aqueous solution.